Informatics solutions for bridging the gap between clinical and laboratory services in a low-resource setting - Julia Driessen; Henry Limula; Oliver J. Gadabu; Gervase Gamadzi; Edwin Chitandale; Anne Ben-Smith; Noor Alide; Gerald P. Douglas (AOSIS, 2015)
Background: There has been little formal analysis of laboratory systems in resource-limited settings, despite widespread consensus around the importance of a strong laboratory infrastructure. Objectives: This study details the informational challenges faced by the laboratory at Kamuzu Central Hospital, a tertiary health facility in Malawi; and proposes ways in which informatics can bolster the efficiency and role of low-resource laboratory systems. Methods: We evaluated previously-collected data on three different aspects of laboratory use. A four-week quality audit of laboratory test orders quantified challenges associated with collecting viable specimens for testing. Data on tests run by the laboratory over a one yearperiod described the magnitude of the demand for laboratory services. Descriptive information about the laboratory workflow identified informational process breakdowns in the pre-analytical and post-analytical phases and was paired with a 24-hour sample of laboratory data on results reporting. Results: The laboratory conducted 242 242 tests over a 12-month period. The four-week quality audit identified 54% of samples as untestable. Prohibitive paperwork errors were identified in 16% of samples. Laboratory service workflows indicated a potential process breakdown in sample transport and results reporting resulting from the lack of assignment of these tasks to any specific employee cadre. The study of result reporting time showed a mean of almost six hours, with significant variation. Conclusions: This analysis identified challenges in each phase of laboratory testing. Informatics could improve the management of this information by streamlining test ordering and the communication of test orders to the laboratory and results back to the ordering physician.